The Influence of Perceived Ease of Use and Perceived Benefits on Purchase Intention with Consumer Trust as an Intervening Variable in Shopee E-Commerce Using the TAM Method - Syauqi Ilal Jinan, Achmad; Ayu Wijayanti, Astrid; Suharyanto, Suharyanto (Dinasti International Journal of Management Science, 2024)
Due to advanced technological developments, customers' interest in conducting research is increasingly changing. Purchases using technology are increasingly varied with specific variables. Purpose: This research analyzes the influence of perceived ease of use and perceived usefulness on purchase intention with consumer trust as mediation in Shopee e-commerce. Methodology This quantitative research used a sample of 130 respondents, whose data was collected using a questionnaire. The analysis technique was carried out using structural equation modeling. Findings From the results of the data analysis that has been carried out, the variables perceived ease of use and perceived usefulness have a significant effect on consumer trust. The variables perceived ease of use and trust significantly affect purchase interest, while the perceived benefit variable does not. Then, the variable's perceived ease of use and perceived benefits significantly affect buying interest through consumer trust. Keywords: Ease of Use, Benefits, Trust, Buying Interest, TAM.